Degradación fotocatalítica de detergentes en efluentes domésticos - Visitación, Lizardo (2005)
Sodium dodecilbenzensulfonate, main tensoactive present in commercial detergents, was selected as model molecule to study degradation of domestic and industrial laundry wastewater samples by advanced oxidative processes using H2O2/ TiO 2/UV system in fluidized bed reactor. Catalyst was studied by X-Ray; main chemical parameters measured were ionic pair methylene blue - LAS, DQO, dissolved C02 ; CI, SO4 -2, CO3 2;  N03, Fe3 +  and bioassays with Daphnia magna.